The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1513/annalsats.201305-134oc
|View full text |Cite
|
Sign up to set email alerts
|

STOP-BANG Questionnaire Performance in a Veterans Affairs Unattended Sleep Study Program

Abstract: The STOP-BANG questionnaire alone is insufficient to confirm the presence of significant sleep apnea. A maximal score of 8 did not have a high enough positive predictive value to forego confirmatory sleep testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
15
1
Order By: Relevance
“…Two OSA clinical prediction rules that have been widely used are the STOP-BANG (11) and MNC (6,10,13), likely because of their simplicity and ease of calculation. Consistent with prior studies on these tools, we found that they both indeed have high sensitivity, but suffer from low specificity (12,34,35), particularly the STOP-BANG questionnaire. Their 1LRs were less than 2 in all three of our patient groups and therefore use of these tools did not result in any substantial change in the probability of having OSA in any particular patient (36).…”
Section: Original Researchsupporting
confidence: 90%
“…Two OSA clinical prediction rules that have been widely used are the STOP-BANG (11) and MNC (6,10,13), likely because of their simplicity and ease of calculation. Consistent with prior studies on these tools, we found that they both indeed have high sensitivity, but suffer from low specificity (12,34,35), particularly the STOP-BANG questionnaire. Their 1LRs were less than 2 in all three of our patient groups and therefore use of these tools did not result in any substantial change in the probability of having OSA in any particular patient (36).…”
Section: Original Researchsupporting
confidence: 90%
“…Kunisaki et al (2014) did not find high specificity or PPV even at high STOP-BANG thresholds of ≥7 or 8. This could be due to their use of a different AHI cutoff of 15 or above to diagnose OSA.…”
Section: Discussioncontrasting
confidence: 55%
“…Another study done by Kunisaki et al (2014) looked at STOP-BANG Questionnaire performance in a Veterans Affairs unattended sleep study program used peripheral arterial tonometry (PAT) to diagnose OSA while our study used type III portable equipment (Collop et al 2011) that is more commonly used and has more studies are available validating its use in clinical practice (Collop et al 2011). Kunisaki et al (2014) did not find high specificity or PPV even at high STOP-BANG thresholds of ≥7 or 8.…”
Section: Discussionmentioning
confidence: 80%
“…In our study, best sensitivity and specificity were seen at 4 or 5 positive answers for moderate OSA, and 4 answers for severe OSA. In a study performed in army veterans [24], raising the STOP-Bang score from 3 to 5 led to slight decrease in sensitivity, increase in specificity and PPV in screening for moderate OSA. Cowan et al found that for AHI > 5 and AHI > 15 cut-off, the best overall accuracy and PPV was at STOP-Bang of 3 or 6 [40].…”
Section: Discussionmentioning
confidence: 97%